2015
DOI: 10.1007/978-3-319-17121-0_84
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Retinal Development via the Epigenetic Modification of Histone H3

Abstract: We are interested in the roles of epigenetic mechanisms in retinal development. By ChIP-qPCR using whole retinal extracts at various developmental stages, we found that the levels of methylation of histones H3K27 and H3K4 and acetylation of histone H3 at specific loci in various genes, which play critical roles in retinal proliferation and differentiation, changed dramatically during retinal development. We next focused on the roles of H3K27 trimethylation in retinal development. Ezh1 and Ezh2 are methyltransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Although a redundant phenotype was observed in loss of function of Utx or Jmjd3 , Jmjd3/Utx-cDKO mice did not show complete loss of PKCα-positive rod-ON-BCs. 37 In this study, we observed reductions in the numbers of ACs and RGCs in the Jmjd3-cKO retina. Although both demethylases are strongly expressed in postnatal RGCs and ACs, the Jmjd3/Utx-cDKO retina showed a reduction, but not a complete loss, of RGCs and ACs; currently, we do not know the underlying mechanism.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Although a redundant phenotype was observed in loss of function of Utx or Jmjd3 , Jmjd3/Utx-cDKO mice did not show complete loss of PKCα-positive rod-ON-BCs. 37 In this study, we observed reductions in the numbers of ACs and RGCs in the Jmjd3-cKO retina. Although both demethylases are strongly expressed in postnatal RGCs and ACs, the Jmjd3/Utx-cDKO retina showed a reduction, but not a complete loss, of RGCs and ACs; currently, we do not know the underlying mechanism.…”
Section: Discussionsupporting
confidence: 49%
“…Utx is another H3K27me3-specific demethylase that is expressed in the INL and GCL during retinal development. 37 We found that the numbers of BRN3B-positive RGCs and TFAP2A-positive ACs were not reduced in the Utx-cKO retina ( Supplementary Figs. S5 A–D).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…While its underlying mechanisms remain uncertain, in part, this is unlikely to be caused solely by the spatiotemporal dynamics and cooperative functionalities of other HMTs and demethylases. Among the two HMTs that regulate H3K27 trimethylation, Ezh1 and Ezh2 , and the demethylase Jmjd3 , Ezh2 and Jmjd3 are widely expressed in retinal progenitors during development; Ezh1 is expressed only weakly in the postnatal retina 29 . The transient expression of Ezh2 during development, which is completely repressed postnatally in the retina, was also confirmed during human retinal development 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the role of UTX during retinal development by the loss of function of UTX using in vivo and ex vivo retinal differentiation systems. We previously obtained preliminary results showing that the loss of UTX in the retinal explant resulted in the failed differentiation of PKCα‐positive rod ON‐bipolar cells (Watanabe & Murakami, 2016). In this study, like JMJD3, we found that the loss of UTX also resulted in a reduced number of PKCα‐positive rod ON‐bipolar cells.…”
Section: Introductionmentioning
confidence: 99%